2020
DOI: 10.1016/j.celrep.2020.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Crosstalk between the LSD1 Demethylase and HDAC1 Deacetylase in the CoREST Complex

Abstract: Highlights d The activities of LSD1 and HDAC1 are closely coupled in the CoREST complex d Both LSD1 and HDAC1 exist in two different kinetic states d CoREST has a bi-lobed, flexible structure with the two enzymes located at opposite ends d CoREST interacts with methylated nucleosomes via LSD1, but not HDAC1 or RCOR1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 56 publications
(82 reference statements)
1
91
1
Order By: Relevance
“…Lsd1 acts, in the majority of cases, to remove mono-or di-methylation on lysine 4 of histone H3 (H3K4me1/me2) (7). It does so in a complex with Histone Deacetylase 1/2 (HDAC1/2) and Corepressor of REST (CoREST) in order to repress target genes (8)(9)(10)(11)(12)(13)(14). In other cases, however it has been shown that Lsd1 is involved in demethylation of H3K9 or H4K20 and can act as a transcriptional co-activator (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Lsd1 acts, in the majority of cases, to remove mono-or di-methylation on lysine 4 of histone H3 (H3K4me1/me2) (7). It does so in a complex with Histone Deacetylase 1/2 (HDAC1/2) and Corepressor of REST (CoREST) in order to repress target genes (8)(9)(10)(11)(12)(13)(14). In other cases, however it has been shown that Lsd1 is involved in demethylation of H3K9 or H4K20 and can act as a transcriptional co-activator (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…An offline multi-angle light scattering (MALS) instrument is also available on the beamline. MALS provides an independent scattering-based measurement of the size, polydispersity and molecular weight of samples along with SAXS data (Behrens et al, 2020;Song et al, 2020).…”
Section: 32mentioning
confidence: 99%
“…When recruited to the CoREST complex, LSD1 catalyses the removal of activating mono- and di-methyl marks on nucleosomal H3K4 residues, resulting in transcriptional repression [ 169 , 170 ]. Studies have revealed a key functional interplay (or “crosstalk”) between HDAC and LSD1 within the complex, where the enzymes mutually influence each other’s activity via the CoREST protein [ 171 , 172 ]. HDAC inhibition has been shown to attenuate LSD1 activity [ 171 , 173 ], plus, synergistic effects of combined HDAC and LSD1 inhibition have been reported [ 174 , 175 , 176 , 177 ].…”
Section: Hdac Complex-selective Dual Inhibitorsmentioning
confidence: 99%